Portraying Peaceful Coexistence and Mutual Tolerance Between Santri and Chinese Community in Lasem - Mohamad Sobirin (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2017)
Coexistence and tolerance among the elite religious leaders in many cases seem not being considered as a problem, but at the grassroots level, the conflict often happened as an ironic phenomenon. This paper reveals and elaborates the socio-religious relations that existed between Santri and Chinese communities in Lasem—a small town located in the northern coastal part of the east end of the Central Java Province. The history recorded Lasem as one of the most important cities in Indonesia that bridged trading with China as early as the 14th century. It explains why Tionghoa villages (pecinan), as well as plenty of Konghucu’s religious worshipping sites (klenteng), could be found in the town and also legacy sites as a place of religious worshipping of Konghucu. On the other hand, Muslims with a strong religious level largely grew in this town. With the qualitative approach, this research found that there are some factors contributing to build six models of coexistence, tolerance, and respect for the socio-religious diversities among the societies as the attitudes toward plural societies which brought into socio-harmony of Lasem. The analyzed data obtained through observation and interviews with various parties which is the object of this research, such as Islamic masters (kyai) and students (santri) at Islamic boarding school (pesantren) in Lasem, community and religious leaders of Chinese-Confucianism, and also documents that describe the historicity of Muslims and Chinese in Lasem.